2020
DOI: 10.1038/s41571-019-0316-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic approaches for small-cell lung cancer

Abstract: Immune-checkpoint inhibitors (ICIs) are approved in the first-line and third-line settings for patients with extensive-stage or relapsed small-cell lung cancer (SCLC), respectively. In the firstline setting, the addition of the anti-programmed cell death 1 ligand 1 (PD-L1) antibody atezolizumab to chemotherapy improves overall survival (OS). In patients with relapsed disease, data from nonrandomized trials have revealed promising responses, although a significant improvement in OS over that obtained with conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
178
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(197 citation statements)
references
References 54 publications
1
178
0
2
Order By: Relevance
“…Since SCLC has a very short survival time, new treatment strategies are urgently needed. The clinical efficacy of immunotherapies has been observed in patients with refractory or metastatic SCLC [12,[19][20][21][22][23]. The phase II KEYNOTE-158 study [21] showed that the PFS of pembrolizumab for relapsed SCLC was 2.0 months, the median OS was 9.1 months, and the one-year PFS and OS were 16.8% and 40.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since SCLC has a very short survival time, new treatment strategies are urgently needed. The clinical efficacy of immunotherapies has been observed in patients with refractory or metastatic SCLC [12,[19][20][21][22][23]. The phase II KEYNOTE-158 study [21] showed that the PFS of pembrolizumab for relapsed SCLC was 2.0 months, the median OS was 9.1 months, and the one-year PFS and OS were 16.8% and 40.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…SCLC occurs primarily in heavy smokers, but despite the very high mutation burden (810) from SCLC genomes predicted to contribute an ample supply of neoantigens, SCLCs express low levels of major histocompatibility complex class I (MHC I) proteins to present tumor-specific antigens (11, 12). This could explain why, among various types of cancer, checkpoint-blockade immunotherapy (CBI) underperforms in SCLC (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…P 3 -QDs-anti-CD8 and P 3 -ErNPs-anti-PD-L1 for Molecular Imaging of Immunotherapy Next, we explored P 3 -QDs for NIR-IIb molecular imaging. Despite the successful application of checkpoint blockade therapy in aw ide range of tumor types, [16] many patients fail to respond to the therapy, [17a] often associated with limited infiltration of CD8 + cytotoxic Tlymphocytes (CTLs). [17b,c] To investigate PD-L1 + tumor cells and CD8 + CTLs simultaneously in vivo,w ep erformed two-plex NIR-IIb molecular imaging using P 3 -QDs-anti-CD8 and ErNPs-anti-PD-L1 by detecting emission at % 1600 nm for both types of probes.The drastically different fluorescence lifetimes of P 3 -QDs and ErNPs were utilized to differentiate the two probes and their respective molecular targets for two-plex molecular imaging in the NIR-IIb window (see Supporting Information).…”
Section: Rapidly Excretable P 3 -Qds For Nir-iib Imagingmentioning
confidence: 99%